McDowell and Naïve realism. Mind and World facing the argument from illusion - Saharrea, Juan (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article rebuilds, through conceptual analysis, some of the aspects in Mind and World of John McDowell aimed at broadening the explanatory role of “the unboundedness of the conceptual” thesis. In order to achieve this, the aforesaid thesis –which runs the risk of being object of the idealism’s objection in its “most pernicious” variants has been connected with the idea of perception as “openness to the world”– which decidedly denies a similar idealism. Although the defense of the perceptual content’s justifying role acknowledges this last thesis, it does not show possible connections with the first one (at least, not in an explicit way). This article, on the contrary, aims at easing this tension, thereby rebuilding McDowell conceptualism’s answer to the argument from illusion. Thus, the conclusion drawn from the distinction between the ordinary possibility of the perceptual error and possibility in principle (of perceptual error) –derived from McDowell’s treatment of perceptual incorrigibility– is that “the unboundedness of the conceptual” and the assertion that perception provides us with direct knowledge of the world’s facts are not incompatible under the perspective of the ordinary possibility.